The Role of Advanced Age and Duration of Infertility on Oocyte Number Retrieved during In Vitro Fertilization - Hendy Hendarto (Universitas Airlangga, 2014)
Introduction: The number of oocytes retrieved during in vitro fertilization related to the success of pregnancy. Today in vitro fertilization has been considered as definitive therapy for infertility problem. Age and duration of infertility is an important factor in infertility that should be evaluated in detail. The purpose of this study was to clarify the role of age and duration of infertility on the number of oocytes retrieved during in vitro fertilization.Method: This was an analytic observational study, including infertile female patients who followed the in vitro fertilization program at Fertility Clinic Graha Amarta Dr Soetomo Hospital Surabaya. Total sampling was conducted during January 1st-June 30th 2014 and found 66 study subjects. Evaluation was performed on age, duration of infertility and the number of oocytes retrieved following ovarian stimulation using FSH and GnRH antagonist injection. All data were analyzed by ANOVA test with level significance of ≤ 0.05.Result: In the group of age <35 years the average number of oocytes retrieved was 9.43 ± 6.29 oocytes, and in the group of age ≥ 35 years averaged number was 6.03 ± 4.67 oocytes. There was significant differences of oocytes number retrieved between the two groups (p = 0.017). The number of oocytes retrieved in group of duration of infertility 1-2 years, 3-4 years and ≥ 5 years were 13.40 ± 3.28 ; 8.64 ± 6.80 and 6.82 ± 5.45, respectively. There was significant differences of oocytes number retrieved between the three groups of duration of infertility (p = 0.017).Discussion: The advanced of age and the longer duration of infertility may contribute to the incidence of the less number of oocytes retrieved in infertile women who follow in vitro fertilization.